An exploratory study on the marketing strategies adopted by small micro and medium enterprises in Johannesburg Central Business District - Mapila, K; Chiliya, N; Chiliya, W (My University, 2014)
Over the years marketing theory development has been limited and small enterprises often have to rely on marketing models used in big businesses. There are a number of marketing strategies that are currently applied by large companies in South Africa which cannot be implemented by small retailers. This is because of the complexity of some of the marketing strategies alluded above are not suited to small retailers because of their limited educational background and resources. Facing the problem of intense competition, SMME entrepreneurs often have to rely on price and other short term strategies to market and sell their products to the ultimate consumer. Entrepreneurs are constantly faced with challenges that restrict their productivity and economic potential. SMMEs face the challenge of marketing their products and services properly to the right markets in order to get returns from their investments. The data for the study was collected by means of interviews. The study used a judgemental sampling. Findings from the study prove that entrepreneurs rely on word of mouth, reducing prices and other low cost promotional strategies for marketing and sale purposes. The findings indicate that it might be useful for SMME’s to change their promotional strategies to suit the South African consumer market to ensure long term profitability
Keywords: Marketing Strategy; Small, micro and medium enterprises